PENERAPAN STRATEGI PEMBELAJARAN POINT-COUNTERPOINT PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Maria Magdalena Duha (Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to determine the improvement of student learning outcomes in the subjects of Pancasila and Citizenship Education by treading the steep path of human rights enforcement in Indonesia through the application of point-counterpoint learning strategies. The implementation of Classroom Action Research (CAR) was carried out in two cycles. The research subjects were 36 students of class XI-IPS2 SMA Negeri 1 Telukdalam in the academic year 2020/2021. The results showed that students were enthusiastic in conducting debate activities and were able to convey their arguments. The average student learning outcomes in the first cycle was 65.9 with the number of students who completed 15 (fifteen) students with a percentage of 41.7% and 21 (twenty one) students who did not complete with a percentage of 58.3%. In the second cycle as many as 80.8 with the number of students who completed 33 (thirty three) people with a percentage of 91.7% and 3 (three) students who did not complete with a percentage of 8.3%. So it can be concluded that the point-counterpoint learning strategy can improve student learning outcomes on human rights material. Suggestions put forward by researchers are (1) teachers should use point-counterpoint learning strategies in learning activities, (2) students should be able to convey their arguments in learning activities so that learning outcomes can be achieved in accordance with research objectives.